(untitled) (Academicia Globe: Inderscience Research, 2021)
This article examines some of the methodological aspects of the formation of the concept of number and magnitude in preschoolers. Emphasizing that counting is a mathematical concept, this is an operation aimed at determining how many elements a given finite set contains, methodological features are given for the development of ideas about the natural series of numbers, a technique for the formation of the ability to group objects (2-6 years), the formation of ideas about the plurality and singularity of objects (from 3 to 5 years old), the formation of the ability to highlight 1 and many objects in the environment (from 3 to 4 years old), as well as the method of teaching counting (4-6 years old). based on a comparison of two groups of objects in terms of quantity.